Workplace health and safety: managing the risk of workplace bullying - Squelch, Joan; Guthrie, Robert (School of Business Law, Curtin Business School, Curtin University of Technology, 2012)
Workplace bullying is a threat to work health and safety. Bullying can create an unsafe, hostile, and threatening working environment. This article addresses workplace bullying in the context of health and safety laws with particular reference to the application of key provisions of the new model Work Health and Safety Act. To ensure a safe work environment, businesses have a duty and responsibility under work health and safety legislation to proactively manage risks, which includes a comprehensive and systematic approach to identifying, assessing, controlling and monitoring workplace bullying. Importantly, businesses have a duty to educate employees about their responsibilities in relation to workplace bullying.